2022
DOI: 10.1227/neu.0000000000002080
|View full text |Cite
|
Sign up to set email alerts
|

Association of Language Barriers With Process Outcomes After Craniotomy for Brain Tumor

Abstract: BACKGROUND:Little is known about the independent association of language barriers on postoperative process outcomes after craniotomies.OBJECTIVE:To evaluate the association of limited English proficiency (LEP) with length of stay (LOS), discharge disposition, hospitalization costs, and rate of 30-day readmission after craniotomy for brain tumor.METHODS:This is a retrospective cohort study of adult patients who underwent craniotomies for brain tumor from 2015 to 2019 at a high-volume neurosurgical center. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were observational, and 26 of 29 studies were retrospective. All were cohort studies except for 1 cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the adverse effect of language barriers on patient care has been explored in other pathologies, the authors here examine this effect on patients undergoing craniotomy for tumor resection at their institution. 1 Their results indicated that limited English proficiency was associated with extended length of stay, increased cost of hospitalization, and increased likelihood of discharge to a skilled care facility after surgery. These findings are consistent with previously reported outcomes for hospitalized patients with lower English proficiency.…”
mentioning
confidence: 99%
“…The authors here have investigated how a barrier between patients and their providers affects the hospital course for patients undergoing craniotomy for brain tumors at their institution. 1…”
mentioning
confidence: 99%